2017
DOI: 10.1515/humor-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

The stability of laughter

Abstract: This article synthesizes a broad body of research in order to propose a concise overview of how laughter functions as a heuristic for social situations and cultural artifacts. It argues that all laughter is indelibly associated with positivity. Phenomena traditionally interpreted as contradicting this claim – such as malicious laughter and pathological laughter – only serve to reinforce an understanding we are born with which connects laughter to positivity. I argue that laughter is perceived as positive or ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Prior research has established that perceiving a partner uses such humor is related to being more satisfied with the relationship (Hall 2017). A variety of explanations have been proffered that might explain this link, including the inherent positivity of laughter (Nikopoulos 2017), the potential of humor as a coping strategy (Lefcourt 2001), and the role of humor in creating common ground (Averbeck 2013). Empirical support for these pathways continues to accumulate as research has explored mechanisms linking these two phenomena.…”
Section: Partner Humor Use and Relationship Satisfactionmentioning
confidence: 99%
“…Prior research has established that perceiving a partner uses such humor is related to being more satisfied with the relationship (Hall 2017). A variety of explanations have been proffered that might explain this link, including the inherent positivity of laughter (Nikopoulos 2017), the potential of humor as a coping strategy (Lefcourt 2001), and the role of humor in creating common ground (Averbeck 2013). Empirical support for these pathways continues to accumulate as research has explored mechanisms linking these two phenomena.…”
Section: Partner Humor Use and Relationship Satisfactionmentioning
confidence: 99%
“…For example, education could inform managers and employees that laughter does not confirm acceptance of a joke. Rather, it may be more of a coping mechanism (Nikopoulos, 2017). Similarly, managers and employees should be educated on the impact of failing to include co-workers in social gatherings outside of work.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the results on humor types showed that the participants' sense of humor usually targeted being happy. Considering that laughter evokes positive emotions on people (Nikopoulos, 2017), making positive humor in workplaces positively affects the mood of the employees (George & Jones, 2012).…”
Section: Discussionmentioning
confidence: 99%